Combining volatilomics and untargeted metabolomics revealed the important role of sinigrin in flavor development of Zhacai - Wenfeng Li; Fangtian Bao; Yimeng Wang; Chan Liang; Wanjie Zhang; Jian Ming (Food Chemistry: X)
Zhacai is a traditional Chinese pickled vegetable. Research has yet to explore the potential role of inherent glucosinolates in the flavor formation of Zhacai. This study employed volatilomics and untargeted metabolomics to investigate the effect of sinigrin on Zhacai flavor. The results confirmed the impact of lactic acid bacteria (LAB) on the quality of Zhacai, while also revealing, for the first time, how sinigrin affects its flavor, color, and pH level. In addition, sinigrin influenced the microflora in Zhacai fermented with and without LAB. Sinigrin significantly impacted the 2,4,6-cycloheptatrien-1-one, 2-hydroxy-4-(1-methylethyl)-, galbetal1,3GlcNAc, and 10E,12Z-octadecadienoic acid flavor compounds in the Zhacai, which exhibited a positive correlation with its flavor quality, while 2-isothiocyanatoethyl-benzene, 1-hepten-3-one, and 10-undecenal demonstrated a negative association. These findings emphasized the importance of monitoring the levels of sinigrin and its hydrolytic products to regulate Zhacai flavor quality.